Recycling photovoltaic silicon waste for fabricating porous mullite ceramics by low-temperature reaction sintering. Issue 12 (September 2021) - Liu, Ruipeng; Xiang, Daoping
Abstract: In this study, porous mullite ceramics with coral-like structures were fabricated at a low temperature of 900 °C by using photovoltaic silicon waste (PSW) as the silicon source directly. The effects of additive content and sintering temperature on the mullitization reaction of green bodies were studied. The results showed that ammonium molybdate tetrahydrate molybdenum (H24 Mo7 N6 O24 ·4H2 O) as an additive could reduce the reaction temperature for mullitization from 1100 °C to 900 °C. The research on the influence of catalyst on material properties showed that porous mullite ceramics with a flexural strength of 52.83 MPa, a 41.78 % porosity, a sintering expansion rate of 0.49 % and an average pore size of 0.23 μm could be fabricated by introducing 7.5 % H24 Mo7 N6 O24 ·4H2 O at the sintering temperature of 1000 °C. This study develops an environment-friendly recycling method of PSW and provides a new idea for the low-cost preparation of porous mullite ceramics with high purity.